STUDY OF EPIDEMIOLOGY AND ITS PROGNOSTIC FACTORS FOR EXPECTED THERAPEUTIC MANAGEMENT OUTCOME ALONG WITH THE ANTIHYPERTENSIVE DRUG PATTERN FOR PREECLAMPSIA IN RURAL SETTING (International Journal of Pharmaceutical Sciences and Drug Research, 2023)
This study analyses the association between epidemiological factors and preeclampsia and the antihypertensive drug pattern used at different stages of preeclampsia. Total 252 patients were enrolled for study. Some of the study variables which were studied was maternal age, history of infertility, family income, education, antihypertensive drug used, body mass index of mother and baby’s birth weight. Study was performed SGT Hospital, Gurugram and was given ethical clearance by the Institutional Ethical Committee (IEC). Data was collected with the help of validated questionnaires. Occurrence of Pregnancy Induced Hypertension (PIH) in our study was found to be 47.2%. Maternal age, low socioeconomic status, less education level, >36 weeks of gestation are one of some major factors responsible for PIH. The current study implies that different dosage forms of labetalol was prescribed with P value <0.05.